Analisis Percobaan Superposisi Gelombang Suara Menggunakan Software Audacity - Widodo, Aris; Aisiyah, Muktamar Cholifah; Ningrum, Izza Eka; Annas, Muhamad Azwar; Musfiana, Masria (Lembaga Yasin AlSys, 2022)
Superposition of waves experiment in physics subject need more innovation to dig up student knowledge about the essential of waves in physics. Such innovation is using Audacity software for analyze it. The purpose of this study is to analyze the superposition of sound waves using Audacity software in the wave superposition experiment. The method used is to prepare tools and materials, namely PC/laptop, 250 Hz, 1 kHz audio files and Audacity Software. Then, 250 Hz and 1 kHz audio is sampled in one wave using Audacity after which each audio sample is imported twice and then combined with Audacity software and saved. This is done for different audio frequencies as well. Then, the results of the merger are opened with Audacity and then analyzed and compared with the initial wave. And the resulting superposition of two 250 Hz waves produces an amplitude of twice and 250 Hz and 1 KHz is produced over a 4 ms wave period and the constructive and destructive wave amplitudes depend on the phase of the two waves. Thus, wave superposition experiments using Audacity software facilitate the analysis of superposition results and characterize the period and amplitude properties of waves.